PERILAKU MASYARAKAT TIONGHOA PADA PROSES PEMBANGUNAN DI KOTA LHOKSEUMAWE - STIE Lhokseumawe (Sekolah Tinggi Ilmu Ekonomi Lhokseumawe, 2020)
This article tried to explain the attitude of the chinese ethnic group towards The 2019 Presidential Election. The involvement of Chinesein Lhokseumawe City is an interesting thing study, for the Chinese has been considered as an obstacle to the assimilation process during the New Order era. The Chinese were given the right to vote in the 2019 Presidential Election. This research analized the political behavior of Chinese in the 2019 Presidential Election in Lhokseumawe City. It focused on two important questions namely: First, how is the behavior of ethnic Chinese towards the 2019 Presidential Election in the City Lhokseumawe. Second, what are the factors that influence the political behavior of Chinese in the 2019 Presidential Election in Lhokseumawe City. The research method used to answer those questions was deep interview as the technic of data collection in a qualitative approach (natural setting). The results of the research were: First, the Chinese in Lhokseumawe City had participated with a good level of attendance, and they were enthusiastically invited families to come together to the TPS/ voting vanue.. Chinese were considered to be rational voters, namely in this case prioritizing the ability of candidates for President and Vice President and political parties in their work programs. Politically, they were more inclined to, the Chinese who associate it with the New Order era and the Aceh DOM era. Finally, the factor of ideological similarity of Chinese in Lhokseumawe City, which has been part of the PDI-P, where many Chinese were involved in the PDI-P party.